A Discussion on the Method of Classification of Medical Syndromes in the ICD-10. (August 2014) - Pang, Duanxiao
Abstract A medical syndrome is a group of disease symptoms involving multiple systems and organs, and there are various naming categories. Most of the symptoms listed in the ICD-10 (International Classification of Diseases) are named by transliteration of the surnames of the discoverers, while the clinical doctors in our country often use the "conventional name" or "common name" and other names in the written diagnosis, which may be a problem for the coders. In this paper, by analyzing three situations of the naming structure for syndromes, the author elaborates the direct search method and the code search method, according to the disease classification principles which are commonly used for searching for the disease code of a syndrome, and points out the issues that should be paid attention to in the work of coding disease syndromes. It also analyzes the search methods of several disease syndromes, and provides a reference for medical record administrators to help them in the process of cataloging the diseases.